Early Incised Slabs and Brasses from the London Marblers - Badham, Sally (Reports of the Research Committee of the Society of Antiquaries of London, 1999)
Although the objective of the Monumental Brass Society is to promote the study both of monumental brasses and of incised slabs, research on the two media has proceeded along separate and largely independent lines. This is the first work to combine the stylistic analysis of monumental brasses with incised slabs. Like brasses, incised slabs are susceptible to stylistic analysis to identify workshop groupings. This book identifies existing and recorded Purbeck marble incised slabs from the pre-Black Death London workshops and compares their designs with those of contemporary brasses. The result is a fuller picture than has previously been available of the operations of the London marblers before the Black Death. It suggests that in the late thirteenth century production was on a larger scale than previously believed, and evidence is outlined for the existence of multiple workshops producing brasses and incised slabs in London for much of the period covered by this study.